2016
DOI: 10.1302/2046-3758.58.bjr-2016-0001.r2
|View full text |Cite
|
Sign up to set email alerts
|

The combined effect of administration of intravenous and topical tranexamic acid on blood loss and transfusion rate in total knee arthroplasty

Abstract: ObjectivesTranexamic acid (TXA) is an antifibrinolytic agent used as a blood-sparing technique in total knee arthroplasty (TKA), and is routinely administered by intravenous (IV) or intra-articular (IA) injection. Recently, a novel method of TXA administration, the combined IV and IA application of TXA, has been applied in TKA. However, the scientific evidence of combined administration of TXA in TKA is still meagre. This meta-analysis aimed to investigate the efficacy and safety of combined IV and IA TXA in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 21 publications
0
19
0
2
Order By: Relevance
“…Hemoglobin can show operative blood loss to some extent [21]. The test found that all patients in the 3 groups had different degrees of postoperative hemoglobin loss, but the hemoglobin loss 1 d after the surgery with tourniquet in the second half was signi cantly lower than that in the restrictive use group without tourniquet, but there was no signi cant difference 3 d after the surgery, suggesting that the tourniquet in the second half could reduce the intraoperative blood loss, but there was no signi cant difference in the total blood loss 3 d after the surgery with the other two groups possibly due to the increase of invisible blood loss [30], which was consistent with the study results of Charalambides et al [23]. Analysis of trial results showed no signi cant differences in postoperative visual analogue scores, HSS scores, C-reactive protein, and hemoglobin levels between the limited and no tourniquet use, suggesting that the limited use of a tourniquet can achieve the same effect as no tourniquet use in early postoperative rehabilitation.…”
Section: Discussionmentioning
confidence: 80%
“…Hemoglobin can show operative blood loss to some extent [21]. The test found that all patients in the 3 groups had different degrees of postoperative hemoglobin loss, but the hemoglobin loss 1 d after the surgery with tourniquet in the second half was signi cantly lower than that in the restrictive use group without tourniquet, but there was no signi cant difference 3 d after the surgery, suggesting that the tourniquet in the second half could reduce the intraoperative blood loss, but there was no signi cant difference in the total blood loss 3 d after the surgery with the other two groups possibly due to the increase of invisible blood loss [30], which was consistent with the study results of Charalambides et al [23]. Analysis of trial results showed no signi cant differences in postoperative visual analogue scores, HSS scores, C-reactive protein, and hemoglobin levels between the limited and no tourniquet use, suggesting that the limited use of a tourniquet can achieve the same effect as no tourniquet use in early postoperative rehabilitation.…”
Section: Discussionmentioning
confidence: 80%
“…The analysis was probably underpowered for detecting differences in the rates of thromboembolic complications, so large cohort studies are required. However, the safety of TXA for any dose, timing or route of administration has been confirmed in numerous meta‐analyses . Moreover, comprehensive venous thromboembolism prevention strategies may be another possible explanation for the lack of additional thromboembolic complications.…”
Section: Discussionmentioning
confidence: 99%
“…Tranexamic acid (TXA) can inhibit fibrinolysis by blocking the lysine‐binding sites on plasminogen . The efficacy and safety of TXA, administered intravenously, intra‐articularly, orally, or via a combination of these routes, have been established in numerous meta‐analyses . Our randomized controlled trial (RCT) demonstrated that 2 g of oral TXA administered 2 h preoperatively produced equivalent reductions in blood loss and hemoglobin (Hb) as 20 mg kg −1 of intravenous TXA administered 5 min preoperatively or 2 g of intra‐articular TXA administered intraoperatively, with a great cost‐saving benefit and greater ease of drug administration .…”
Section: Introductionmentioning
confidence: 95%
“…The results demonstrated that compared to the control group, the combined group had decreased blood loss on postoperative day 1 ( MD , 277 mL; P = 0.002) and day 2 ( MD , 373 mL; P = 0.003). A meta‐analysis compared intravenous or topical TXA alone to the combination of both, which revealed that the combination facilitated less total blood loss, hidden blood loss, drainage volume, a lower transfusion rate, and a lower decline of Hb level ( P < 0.05), and was not associated with a higher risk of wound infection and deep venous thrombosis ( P > 0.05). There is high quality evidence that favors the use of TXA in TKA.…”
Section: Intraoperative Strategiesmentioning
confidence: 99%